Tethering of the Conserved piggyBac Transposase Fusion Protein CSB-PGBD3 to Chromosomal AP-1 Proteins Regulates Expression of Nearby Genes in Humans - Gray, Lucas T. (Public Library of Science, 2012)
The CSB-PGBD3 fusion protein arose more than 43 million years ago when a 2.5-kb piggyBac 3 (PGBD3) transposon inserted into intron 5 of the Cockayne syndrome Group B (CSB) gene in the common ancestor of all higher primates. As a result, full-length CSB is now coexpressed with an abundant CSB-PGBD3 fusion protein by alternative splicing of CSB exons 1–5 to the PGBD3 transposase. An internal deletion of the piggyBac transposase ORF also gave rise to 889 dispersed, 140-bp MER85 elements that were mobilized in trans by PGBD3 transposase. The CSB-PGBD3 fusion protein binds MER85s in vitro and induces a strong interferon-like innate antiviral immune response when expressed in CSB-null UVSS1KO cells. To explore the connection between DNA binding and gene expression changes induced by CSB-PGBD3, we investigated the genome-wide DNA binding profile of the fusion protein. CSB-PGBD3 binds to 363 MER85 elements in vivo, but these sites do not correlate with gene expression changes induced by the fusion protein. Instead, CSB-PGBD3 is enriched at AP-1, TEAD1, and CTCF motifs, presumably through protein–protein interactions with the cognate transcription factors; moreover, recruitment of CSB-PGBD3 to AP-1 and TEAD1 motifs correlates with nearby genes regulated by CSB-PGBD3 expression in UVSS1KO cells and downregulated by CSB rescue of mutant CS1AN cells. Consistent with these data, the N-terminal CSB domain of the CSB-PGBD3 fusion protein interacts with the AP-1 transcription factor c-Jun and with RNA polymerase II, and a chimeric CSB-LacI construct containing only the N-terminus of CSB upregulates many of the genes induced by CSB-PGBD3. We conclude that the CSB-PGBD3 fusion protein substantially reshapes the transcriptome in CS patient CS1AN and that continued expression of the CSB-PGBD3 fusion protein in the absence of functional CSB may affect the clinical presentation of CS patients by directly altering the transcriptional program.